New M-Type Stars Found in the BAO Plate Archive Centered at α = + 15h δ = +580 - Kostandyan, G. R.; Gigoyan, K. S.
The BAO Plate Archive low-resolution spectral plate centered at α = + 15h δ = +580 is analyzed to find new late-type stars. 23 new late-type stars have been detected. New objects were cross-correlated with GAIA DR3, 2MASS, AllWISE, TESS and SDSS catalogues. For the detected objects, we present luminosity classes estimated from Gaia DR3 and 2MASS photometry and available proper motions. The majority of the objects are M dwarfs. Two objects are M giants.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture